Summary of Baseline Household Survey Results: Makueni, Kenya - Mwangangi M; Mutie, Ianetta; Mango, Joash (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
This report presents a summary of the main results of a baseline household survey carried out between April 2012 and June 2012 in seven (7) villages with 140 households (HHs) in Wote, a benchmark site of the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS). Wote is located in Makueni County in South Eastern Kenya. The survey was carried out using the standardised CCAFS household baseline tool.